Diseño de un tablero de control y una guía para integrar sus datos base, en empresas pequeñas de negocios especializados y actividades combinadas. (2018)
In the present project, a Control Board model based on the Balanced Scorecard (BSC) was designed to provide a guide for strategic business management, which allows entrepreneurs to improve decision making and monitor business performance, which can be applied in Colombian small companies that present combined economic activities. The Control Board was built from the review of case studies in which them were implemented in companies belonging to franchises, food traders and product importers. To achieve the final result, the objectives with a similar scope were combined, obtaining a guide of strategic objectives in the financial perspectives, of clients, internal processes and learning and knowledge. As a complement to the model, a guide of recommendations was developed to identify the typical sources of information and the data that supply it. The control board model resulting from the project was tested in a first version, carrying out its application in the company Horneros SAS, chosen as a case study to adapt to the company profile to which the project is focused (small companies of specialized businesses and combined 6 activities). The findings suggest that executives can effectively model strategies for their business, based on the combination of indicators typically used by different companies belonging to the same industrial sector, allowing them to know how competitive advantages can be obtained over other market players.